Dinâmica do emprego industrial no Brasil entre 1990 e 2009: Uma vis\~ao regional da desindustrializaç\~ao - Bruno Oliveira Cruz; Iury Roberto Soares Santos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2011)
– This paper attempts to analyze the process of deindustrialization under a regional aspect. The loss of relevance of the manufacturing sector, as measured by percentage of GDP or total employment, is not neutral in spatial terms. Using the Rais database at the geographical level of micro regions, we find evidence of an industrial econcentration. The gain of relevance of some micro regions, however, seems to be conditioned on the rise of employment in less technological industries, showing that although consolidated regions have lost overall relevance, they continue to lead in the country when one accounts for technological contents of industry.
Keywords: R11; R12; 330; Deindustrialisierung; Fertigungsberufe; Regionalökonomik; Brasilien